2017
DOI: 10.12659/msm.904892
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA (LncRNA) HOXA11-AS Promotes Breast Cancer Invasion and Metastasis by Regulating Epithelial-Mesenchymal Transition

Abstract: BackgroundTo detect the expression of lncRNA HOXA11-AS and its biological effect in breast cancer.Material/MethodsIn this study, fluorescent quantitative real-time PCR (qRT-PCR), MTT assay and clone formation assay, flow cytometry, Transwell assay and wound healing assay, immunofluorescence, and Western blot analysis were conducted to detect the expression of lncRNA HOXA11-AS, cell proliferation activity, cell apoptosis rate and cell cycle distribution, the changes of cell invasion and metastasis capacity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…According to all previous reports, we knew that HOXA11-AS could positively modulate progression and development of several types of human cancers, such as colorectal cancer, 12 hepatocellular carcinoma, 13 glioma 14 and breast cancer. 15 The specific role of HOXA11-AS in lung adenocarcinoma still lacks investigation. In this study, we tried to reveal the specific function and mechanism of HOXA11-AS in lung adenocarcinoma.…”
mentioning
confidence: 99%
“…According to all previous reports, we knew that HOXA11-AS could positively modulate progression and development of several types of human cancers, such as colorectal cancer, 12 hepatocellular carcinoma, 13 glioma 14 and breast cancer. 15 The specific role of HOXA11-AS in lung adenocarcinoma still lacks investigation. In this study, we tried to reveal the specific function and mechanism of HOXA11-AS in lung adenocarcinoma.…”
mentioning
confidence: 99%
“…Li et al showed that HOXA11-AS expression in breast cancer tissue of 50 patients was relatively higher than that in adjacent normal tissues. HOXA11-AS promoted breast cancer invasion and metastasis by regulating epithelial-mesenchymal transition [25]. The expression of HOTTIP was found to be significantly correlated with tumor size, lymph node status, TNM stage and overall survival in the breast cancer patients [26].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, upregulation of FOXD2 Adjacent Opposite Strand RNA 1 has been associated with poor prognosis in various types of tumor (51)(52)(53). HOXA11-AS has been indicated to promote BC invasion and metastasis by regulating EMT (54). Furthermore, LINC00324 acts as an oncogene involved in the tumorigenesis and progression of gastric and lung cancer (55).…”
Section: Discussionmentioning
confidence: 99%